Green synthesis of silver nanoparticles using sun dried tulsi leaves and its catalytic application for 4-Nitrophenol reduction. Issue 1 (February 2018) - Singh, Jagpreet; Mehta, Akansha; Rawat, Mohit; Basu, Soumen
Highlights: A clean and sustainable approach for the synthesis of biogenic silver nanoparticles (AgNPs) from tulsi leaf extract. The utilization of solar radiations at mild temperature conditions for nanoparticles (NPs) formation. Catalytic potential of the NPs was studied for reduction of 4-nitrophenol to 4-aminophenol (100% conversion) in alkaline medium. Reusability of the catalyst exhibited better reduction of the 4-nitrophenol to 4aminophenol even after 5 consecutive cycles. Abstract: The green synthesis of metallic nanoparticles is a highlight of nanotechnology and has gained increased attention due to growing need to develop non-toxic, fast, facile and environmentally friendly synthetic technique. Current work reports a clean and sustainable approach for the synthesis of biogenic silver nanoparticles (AgNPs) from tulsi leaf extract. The uniqueness of this study lies in the utilization of solar radiations at mild temperature condition for AgNPs formation. Spectroscopic and electron microscopic characterization studies revealed, the formation of stable and monodisperse AgNPs with a sharp absorption band at 430 nm and average diameter of 5–10 nm. Catalytic potential of the AgNPs was studied for the reduction of 4-nitrophenol to 4-aminophenol (100% conversion) in alkaline medium. The catalytic conversion was studied by UV–vis spectroscopy with high reduction rate (k = 2.048 min −1 ). Moreover, the reusability of the catalyst exhibited a better reduction of the 4-nitrophenol to 4-aminophenol even after 5 consecutive cycles. So we conclude that green synthesis of AgNPs by tulsi extract is a positive step toward the development of novel catalysts.